Hepatitis associated with infection in Korean children: a prospective study - Kyu Won Kim; Jae Jin Sung; Hann Tchah; Eell Ryoo; Hye Kyung Cho; Yong Han Sun; Kang Ho Cho; Dong Woo Son; In Sang Jeon; Yun Mi Kim (Korean Pediatric Society, 2015)
PurposeMycoplasma pneumoniae (MP) infection is a major cause of respiratory infection in school-aged children. Extrapulmonary manifestations of MP infection are common, but liver involvement has been rarely reported. The aim of this study was to determine the clinical characteristics of MP-associated hepatitis.MethodsThis prospective study included 1,044 pediatric patients with MP infection diagnosed serologically with MP IgM at one medical center from January 2006 to December 2012. Eighty of these patients had elevated levels of serum aspartate aminotransferase (AST) and alanine aminotransferase (ALT), each greater than 50 IU/L, without any other specific liver disorder and were compared with the 964 children without liver disorders.ResultsIn total, 7.7% of patients with MP infection had a diagnosis of hepatitis, especially in fall and winter. The ratio of male to female patients was 1.7:1, and the mean age of the patients was 5 years and 5 months. The most common symptoms were cough, fever, and sputum. Anorexia was the most common gastrointestinal symptom, followed by nausea/vomiting, diarrhea, and abdominal pain. Mean levels of AST and ALT were 100.65 IU/L and 118.73 IU/L, respectively. Serum AST/ALT level was normalized within 7.5 days on average without complications. The mean duration of hospitalization (11.3 days) was longer for children with hepatitis than for those without hepatitis (P=0.034).ConclusionMP-associated hepatitis is not uncommon and has a relatively good prognosis. Therefore, clinicians should be concerned about liver involvement in MP infection but avoid further unnecessary evaluation of hepatitis associated with MP.